Penafsiran Ayat-Ayat Antropomorfisme Menurut Muhammad Ali Ash-Shabuni Dalam Safwah At-Tafasir - Ranti; Muhammad Nuh Siregar (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The interpretation of anthropomorphic verses in the Qur'an, such as "the hand of God" or "the face of God," has generated significant theological debate in the history of Islamic thought. This article aims to analyze Muhammad Ali Ash-Shabuni's approach in interpreting these verses in Safwah at-Tafasir. Using a qualitative method based on literature study and a thematic-comparative approach, this study finds that Ash-Shabuni combines various views of classical mufasirs to build a theological position that maintains the principle of God's transcendence (tanzih) within the framework of the Ahlussunnah wal Jama'ah creed. He interprets the verses of anthropomorphism symbolically or through the submission of meaning to God (tafwidh), without assigning a literal meaning that likens God to creatures. The interpretation of "Allah's hand" is understood as a symbol of His power and defense; "Allah's face" is interpreted as His eternal Essence; while in the context of the Qibla direction, Allah's face is interpreted as His pleasure. This study emphasizes Ash-Shabuni's contribution in bridging between the legacy of classical tafsir and the needs of contemporary readers through a systematic approach in understanding the verses of the nature of God.